DILEMMAS AND LIMITATIONS FOR SYSTEMATIC ADAPTATION AND INSTRUMENTALIZATION OF ORGANIZATIONAL TOOLS IN PRIMARY HEALTH CARE: INTEGRATIVE REVIEW - Victória Garbelini Ribeiro, Anna; Furst Vaccarezza, Gabriela; David, Giovana; Freitas Baueb, Jorge; Bahov Shinnishi, Juliana; Moraes Armesto, Leonardo; Kawamoto DelaTorre, Lucas; Correia Rodrigues Nóvoa, Patrícia; Chaves Reis, Priscila; Roberto Alonso, Thabata (Health and Society, 2023)
The study is based on the need to organize the flow of registration of hypertensive patients, which faces a framework of vestments and limitations that end up generating dilemmas in primary health care, leading to indefinitions, ineffective developments and non-compliance on the part of the team and management involved. Thus, it is expected that there will be an expansion of strategic actions by the health network, in order to allow continuous follow-up to monitor the prognosis of SAH in carriers, aiming at improving the quality of life together with health education, making patients aware of their needs, as well as strengthening the bond between users and the FHS doctor. Thus, the research seeks to see in the literature, the analysis and observations that clarify or analyze the universality of factors that hinder and restrict the development of behaviors and decision-making in an accurate and conclusive way, as it expands the pattern of recognition, dissemination and incorporation in intersectoral practices and interteams of care for the multiplicity of diseases and conditions recorded in the care process in various spheres of health.